Two Birds with One Stone? Implications of conditional assistance in victim protection and prosecution of traffickers - Brunovskis, Anette; Skilbrei, May-Len (Anti-Trafficking Review, 2016)
Protection of victims and prosecution of traffickers are established as core principles in international and national anti-trafficking policies. In this article, we discuss the dilemmas of linking protection of victims (a term that includes social protection) to their cooperation with authorities, using Norway as a case. Our analysis of the Norwegian case is based on interviews with victims of trafficking, social workers, police and prosecutors, and examination of court decisions on cases of trafficking. The linking of protection and prosecution is anchored in international conventions and directives. While this is often framed as a mutual advantage for both protection and prosecution, in reality both goals may suffer. We discuss how the goal of prosecution affects assistance available to different groups of victims. It creates unequal access to assistance and different preconditions for well-being and predictability, depending on how useful their information about traffickers is perceived to be, and police capacity to investigate. We then move on to discuss how the incentive of protection for cooperation is interpreted and dealt with in the justice system. Victims who receive assistance and have a chance of getting permanent residence permits in exchange for their testimonies are considered to be less reliable and credible witnesses. This also brings into question how victims of trafficking are understood and constituted as witnesses. We discuss these issues in light of a broader literature on gender, law and victimhood.